The oecodesignator the ecocentric-environmental design professional - Flor, Enrico G. (2005)
The environmental designs professions are having a difficulty redefining their practice for the next millennium, especially with current circumstances that question the validity and efficacy of their respective practices. A paradigm shift, brought about by concepts from fields outside the environmental landscape profession can contribute to a holistic approach and conduct of their respective practice that will address sustainability of a designed and built project, as well as the true integration of all these professions into what we can call generically as the oecodesignator. Rather than competing professions, the new paradigm espouses the concept that they are all of the same breed, utilizing the same thought processes to attack a spatial and environmental problem, but differing only through the context filter and language that one opts to use.